Atomically Dispersed Metal Atoms: Minimizing Interfacial Charge Transport Barrier for Efficient Carbon-Based Perovskite Solar Cells - Yanying Shi; Xusheng Cheng; Yudi Wang; Wenrui Li; Wenzhe Shang; Wei Liu; Wei Lu; Jiashuo Cheng; Lida Liu; Yantao Shi (Nano-Micro Letters)
Highlights Atomically dispersed metal atoms effectively enhance energy level alignment and reduce energy losses at the electrode interfaces. The optimized carbon-based perovskite solar cells achieve a power conversion efficiency (PCE) of 22.61% and maintain 94.4% of their initial PCE after 1000 h under continuous illumination without encapsulation.